2019
DOI: 10.3390/jcm8071015
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Exergames on Brain Dynamics in Women with Fibromyalgia: A Randomized Controlled Trial

Abstract: Background: Exergames are non-immersive versions of virtual reality that involve physical exercise and have shown several benefits on physical fitness and quality of life in women with fibromyalgia. However, the effects on brain dynamics are still unknown. Aim: the aim was to evaluate the effects of a 24-week exergame intervention on resting brain dynamics in women with fibromyalgia in a single-blinded, randomized controlled trial. Methods: Fifty-six women with fibromyalgia were assessed for eligibility; 55 fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 59 publications
0
31
1
Order By: Relevance
“…Aside from fitness parameters, previous studies of exergames in women with FM reported improvements in health-related quality of life, disease impact, pain, and brain processing [16][17][18][19][20]. The 24 week exergame intervention in this study did not have any significant effect on disease impact.…”
Section: Discussioncontrasting
confidence: 53%
See 2 more Smart Citations
“…Aside from fitness parameters, previous studies of exergames in women with FM reported improvements in health-related quality of life, disease impact, pain, and brain processing [16][17][18][19][20]. The 24 week exergame intervention in this study did not have any significant effect on disease impact.…”
Section: Discussioncontrasting
confidence: 53%
“…The current study focused on the effects of 24 weeks of exergame-based training and a 24-week detraining period in patients with FM. Three articles focusing on quality of life, physical fitness under dual-task conditions, and brain processing were recently published elsewhere [18][19][20]. The hypothesis of the current study was entirely different from previous studies, and included follow-up evaluation.…”
Section: Trial Designmentioning
confidence: 98%
See 1 more Smart Citation
“…Different articles focused on the primary outcomes (i.e., electroencephalography, physical fitness, and quality of life) of the trial have been recently published [32,[36][37][38]. Nevertheless, the hypothesis in the present study is entirely novel (improvements in different volumetric brain structures after an exergame intervention) and significantly differs from the other articles.…”
Section: Trial Designmentioning
confidence: 79%
“…In patients with FM, this type of intervention has been previously used in a nonimmersive version, obtaining improvements in the overall quality of life, pain, disease, mobility, balance, and fear of falling [30,31]. Furthermore, the effects of exergame-based interventions on the brain dynamics of patients with fibromyalgia have previously been studied, finding changes in brain dynamics that could be related to increased cerebral blood flow [32]. On the other hand, two studies have assessed changes in brain structure after exergame training in older adults [33,34].…”
Section: Introductionmentioning
confidence: 99%